2011
DOI: 10.5005/jp-journals-10012-1048
|View full text |Cite
|
Sign up to set email alerts
|

Role of Mini-implants in Orthodontics

Abstract: Anchorage has been a worrisome factor since the origin of orthodontics. Many modalities have been suggested in the scientific literature like extraoral anchorage with head gears, Intraoral anchorage with Nance palatal arches and reinforcement of anchorage units with addition of second molars, etc. Yet, the specialty of orthodontics did not find a solution for this problem until the introduction of miniimplants. Orthodontic implants are different from the ones used for prosthetics as there is no osseointegratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 76 publications
0
2
0
Order By: Relevance
“…According to research by M. Jasmine and colleagues, increasing the insertion angles from 30 to 45 degrees, 60 degrees, and 90 degrees reduced micro-implant and cortical bone displacements [ 21 ]. Studies have also shown that for improved stability and effectiveness when placing a micro-implant within the posterior buccal area of the maxilla and the mandible, mini-screws are advised to be inserted 70 to 80 degrees into the long longitudinal axis of the teeth [ 22 , 23 ]. The greatest retention was achieved when temporary anchoring devices were positioned 90 degrees from the synthetic cortical plate.…”
Section: Discussionmentioning
confidence: 99%
“…According to research by M. Jasmine and colleagues, increasing the insertion angles from 30 to 45 degrees, 60 degrees, and 90 degrees reduced micro-implant and cortical bone displacements [ 21 ]. Studies have also shown that for improved stability and effectiveness when placing a micro-implant within the posterior buccal area of the maxilla and the mandible, mini-screws are advised to be inserted 70 to 80 degrees into the long longitudinal axis of the teeth [ 22 , 23 ]. The greatest retention was achieved when temporary anchoring devices were positioned 90 degrees from the synthetic cortical plate.…”
Section: Discussionmentioning
confidence: 99%
“…Orthodontic mini-implants are considered capable of being an absolute anchor because the reciprocal force from the anterior retraction will be transmitted to the alveolar bone without involving the posterior teeth and is not influenced by patient compliance factors (Antolis et al, 2021). In addition, mini implants in orthodontic can be used to treat intrusion/extrusion of teeth, close edentulous spaces, repositioning of a malposed tooth, reinforced anchorage, partial edentulism, correct undesired occlusion, and orthopedic movement (Nayak and Malviya, 2011;Sheoran et al, 2021).…”
Section: Introductionmentioning
confidence: 99%